Vibrational fingerprint of localized excitons in a two-dimensional metal-organic crystal. Issue 1 (December 2018) - Corva, M.; Ferrari, A.; Rinaldi, M.; Feng, Z.; Roiaz, M.; Rameshan, C.; Rupprechter, G.; Costantini, R.; Dell'Angela, M.; Pastore, G.; Comelli, G.; Seriani, N.; et al.
Abstract Long-lived excitons formed upon visible light absorption play an essential role in photovoltaics, photocatalysis, and even in high-density information storage. Here, we describe a self-assembled two-dimensional metal-organic crystal, composed of graphene-supported macrocycles, each hosting a single FeN4 center, where a single carbon monoxide molecule can adsorb. In this heme-like biomimetic model system, excitons are generated by visible laser light upon a spin transition associated with the layer 2D crystallinity, and are simultaneously detected via the carbon monoxide ligand stretching mode at room temperature and near-ambient pressure. The proposed mechanism is supported by the results of infrared and time-resolved pump-probe spectroscopies, and by ab initio theoretical methods, opening a path towards the handling of exciton dynamics on 2D biomimetic crystals. Long-lived excitons in a two-dimensional metal-organic crystal can be produced by visible light and detected by infrared radiation. Here, the authors show that the excitonic state of a biomimetic macrocycle can be 'read' by measuring the vibrations of an adsorbed ligand.